Mural en homenaje a personajes emblemáticos que enaltecieron la educación y el desarrollo de la provincia de El Oro, en la fachada este del auditorio exterior del nuevo edificio administrativo de la Universidad Técnica de Machala, fundamentada en la Técnica Mixta. - Maza Solano, Héctor Manuel (2013)
When feeling the need as a student of the Arts career, and seeing the reality of culture in the Province, reflected in the Technical University of Machala, which does not have works of a cultural and artistic nature, which identifies with the career Of Arts, the proposal of the realization of a Mural arises, that helps to the strengthening of the Art in the Institution and also to arrive with a message to the studious youth of the Province.